ANALYSIS OF EDDY KINETIC ENERGY AND VERTICAL TEMPERATURE DISTRIBUTION FOR DETERMINING OF FISHING GROUND TUNA IN THE SOUTHERN JAVA - LUTFIYATI (NIM: 22411003); pembimbing: Ivonne M. Radjawane, PhD ; Dr. Ibnu Sofian, M.Eng, INDAH
The complex characteristic of southern waters of Java causes a high chlorophyll-a concentration, which attracts the migration of tuna at certain months. Its abundance in the open ocean is influenced by mesoscale eddies, formed by the presence of Ekman transport and Coriolis force which cause a different gradient of sea water density. Mesoscale eddies affect isotherm layer changes because of the cyclonic movement, while the cyclonic mesoscale eddies will shallow the isotherm layer. The isotherm shallowness can be observed from the vertical temperature distribution in the area where the cyclonic mesoscale eddies occurs. Mesoscale eddies intensity can be studied using seasonal and monthly distribution of eddies kinetic energy (EKE). The EKE intensity and vertical temperature distribution analysis is used to understand the increase in chlorophyll-a concentration as an indication of tuna fishing ground in the southern Java. The problem solving method to determine of the eddy kinetic energy intensity and vertical temperature distribution are employed using 3D ROMS model. The result of model analysis shows the EKE intensity from climatological data in east to transitional II season with an average value of 0.60 m2/s2. Isotherm uplifting as a result of cyclonic mesoscale eddies in the east season is majorly occurred at latitude -10 °LS at temperatures 10-18 °C up to 25-50 meters. The monthly data in 2008 shows increased of EKE during May to October with an average value of 0.60 m2/s2. Isotherm uplifting as a result of cyclonic mesoscale eddies in the east season is majorly occurred at latitude -10 °LS at temperatures 10-20 °C up to 25-70 meters. EKE intensity of climatological and monthly data influenced by Indonesian through flow which strengthened in the east season and is influenced by a seasonal stream in southern Java.